A proposed typology of the military bully - Kalamdien, Donovan; Lawrence, Audrey (Scientia Militaria - South African Journal of Military Studies, 2017)
Workplace bullying is a pervasive problem faced by organisations globally. Although progress has been made in augmenting our understanding of the phenomenon within diverse work settings, the military remains one work environment where dialogue into the phenomenon is not forthcoming. Scientific enquiry into bullying in the military is virtually non-existent. The aim of this study was to provide a conceptual analysis and review of workplace bullying literature, whilst also characterising the personas of military bullies and initiatives to assist them in correcting their behaviour. The associated costs to an organisation necessitate the urgency with which this issue needs to be addressed, especially within the military environment.